Strategic municipal solid waste management: A quantitative model for Italian regions - Cucchiella, Federica; D’Adamo, Idiano; Gastaldi, Massimo (Energy conversion and management, 2014)
•Definition of new plan waste management based on incineration.•Profitability of waste facilities based on economic and financial indicators.•The amount of wastes generated are considered not annually constant and with a regional detail.•A sensitivity analysis is used to test some of the initial assumptions.•Regional strategies are proposed for optimize benefits from correct waste management. Current economic crisis brought to light the structural deficiencies of European economy. This paper aims to improve the performances of a policy on sustainable municipal solid waste management strategies. Specifically, the attention is focused on Italian country that reports a high rate of landfilling. Waste to Energy plant is an attractive technological option in municipal solid waste, but it is a subject of intense debate. Incinerators require effective and efficient controls to avoid emissions of harmful pollutants into the air, land and water, which may influence human health and environment. To address waste management situation, this study uses a multi-objective mathematical programming. A new plan is presented to evaluate and quantify the effects of initiatives for diversion of current waste from landfill. In an attempt to better simulate realistic waste management scenarios, the amount of waste generated is not annually constant and changes are accounted in waste diversion rates. Moreover, due to the geographical characteristics of Italy, the realization of new facilities is replicated with a regional detail. In this paper economic and financial indicators are used to define the profitability of waste facilities. Moreover, a sensitivity analysis is used to test some of the initial assumptions. Once identified the efficient Waste to Energy plant, regional strategies of waste management are proposed to optimize financial and environmental benefits of the sector. The proposed waste management framework provides a concrete scheme for future research in assessing quantitatively the effectiveness of waste management.